Boron removal by electrocoagulation and recovery - Isa, M.H. (Elsevier Ltd, 2014)
This work investigated the removal of boron from wastewater and its recovery by electrocoagulation and hydrothermal mineralization methods respectively. The experimental design was developed using Box-Behnken Model. An initial study was performed based on four preselected variables (pH, current density, concentration and time) using synthetic wastewater. Response surface methodology (RSM) was used to evaluate the effect of process variables and their interaction on boron removal. The optimum conditions were obtained as pH 6.3, current density 17.4mA/cm2, and time 89min. At these applied optimum conditions, 99.7 boron removal from an initial concentration of 10.4mg/L was achieved. The process was effectively optimized by RSM with a desirability value of 1.0. The results showed that boron removal efficiency enhanced with increase in current density and treatment time. Removal efficiency also increased when pH was increased from 4 to 7 and subsequently decreased at pH 10. Adsorption kinetics study revealed that the reaction followed pseudo second order kinetic model; evidenced by high correlation and goodness of fit. Thermodynamics study showed that mechanism of boron adsorption was chemisorption and the reaction was endothermic in nature. Furthermore, the adsorption process was spontaneous as indicated by negative values of the adsorption free energy. Treatment of real produced water using electrocoagulation resulted in 98 boron removal. The hydrothermal mineralization study showed that borate minerals (Inyoite, Takadaite and Nifontovite) can be recovered as recyclable precipitate from electrocoagulation flocs of produced water. Â© 2013 Elsevier Ltd.